Closing the financial access gap: Pawnshop’s hybrid strategy as a model for equitable economic inclusion - Triaswari Ayunandini; Asnia Sundari; Revie Nevilla Extin; Ririn Ayu Safitri; Afrizal Fauzi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Digital financial transformation has not fully yielded functional financial inclusion, particularly among unbanked and underbanked populations in non-urban areas and underserved regions. Fully digital service approaches risk generating second-level digital divides stemming from limited digital literacy, infrastructural deficiencies, and low user trust. This study aims to analyze the implementation of PT Pegadaian's hybrid strategy in advancing substantive financial inclusion and equitable economic empowerment. Methods: This study employs a systematic literature review (SLR) following PRISMA guidelines via lens scholar. Of 1,337 identified articles, 26 met inclusion criteria and were analyzed through thematic analysis guided by the perspectives of substantive financial inclusion and distributive justice. Findings: Pegadaian's hybrid strategy implementation confronts three barrier clusters constituting a digitalization paradox: structural barriers within agent networks, urban-biased interfaces on digital platforms, and real-time O2O integration desynchronization. In response, this study formulates the equitable seamless hybrid framework (ESHF), integrating the reconstruction of agents' roles as financial literacy consultants, lite-mode platform optimization, and O2O synchronization grounded in the principle of Hifz al-Mal, with the potential to reduce information asymmetry and lower MSME capital costs. Conclusion: The ESHF model repositions hybrid strategy as a strategic instrument for institutionalizing economic justice through a high-tech, high-touch approach oriented toward distributive justice, rather than a mere operational-technical option. Novelty/Originality of this article: The originality of this study lies in the formulation of ESHF, which transcends conventional omnichannel approaches through the integration of user-needs-driven AI agent autonomy, lite-mode platforms, and O2O synchronization within the moral framework of Hifz al-Mal, offering a new interdisciplinary approach to the study of hybrid strategies in public financial institutions operating within developing economies.